Susceptibility to mycobacterial disease due to mutations in IL-12Rβ1 in three Iranian patients - Alinejad Dizaj, Maryam; Mortaz, Esmaeil; Mahdaviani, Seyed Alireza; Mansouri, Davood; Mehrian, Payam; Verhard, Els M; Varahram, Mohammad; Babaie, Delara; Adcock, Ian M; Garssen, Johan; van de Vosse, Esther; Velayati, Aliakbar (Springer Science and Business Media Deutschland GmbH, 2018)
In the last decade, autosomal recessive interleukin-12 receptor β1 (IL-12Rβ1) deficiency, the most common cause of Mendelian susceptibility to mycobacterial disease (MSMD), has been diagnosed in a few children and adults with severe tuberculosis in Iran. Here, we report three cases referred to the Immunology, Asthma and Allergy ward at the National Research Institute of Tuberculosis and Lung Diseases (NRITLD) at Masih Daneshvari Hospital from 2012 to 2017 with Mycobacterium tuberculosis and non-tuberculous mycobacteria infections due to defects in IL-12Rβ1 but with different clinical manifestations. All three were homozygous for either an IL-12Rβ1 missense or nonsense mutation that caused the IL-12Rβ1 protein not to be expressed on the cell membrane and completely abolished the cellular response to recombinant IL-12. Our findings suggest that the presence of IL-12Rβ1 deficiency should be determined in children with mycobacterial infections at least in countries with a high prevalence of parental consanguinity and in areas endemic for TB like Iran.
Keywords: SDG 3 - Good Health and Well-being